A greenhouse for the amateur - Wells, Ora Rebecca (My University, 1892)
Introduction: A properly constructed and wellkept greenhouse is a source of delight to all who enter it. Those of us who have none of our own visit that of another and delight in the variety of beautiful foliage and flowers, and the sweet delicious summer atmosphere. The owner of the greenhouse delights in the artistic arrangement of his plants, in the different varieties he has produced for himself, and us showing to others the beauty of his flowers, the successful results of his works. During our long severe winters here in Harreas, there is no place where we will sooner forget that outside the snow is drifting and the thermometer standing at 20 below zero than in the so called green house. There is no place where we more quickly get thoroughly “thawed out” and forget but that it is summer as among the plants in the flower scented atmosphere and even temperature of the greenhouse. To build a greenhouse the first thing to think of is the situation, and in so doing the amateur should remember that the questions of accessibility and drainage are of great importance. The house, of course, if not joining the dwelling house should be placed near it, in an open sunny apot and where the soil is well drained.
Citation: Wells, Ora Rebecca. A greenhouse for the amateur. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Greenhouse; DIY; Green thumb; Construction; Botany; Farm; Theses; Manuscripts (documents)